Patristic theories of biblical interpretation: the Latin fathers - Toom, Tarmo (Cambridge University Press, 2016)
This volume provides an in-depth analysis of patristic hermeneutics for those who research, teach, or study the early church and the interpretation of Scripture. It focuses exclusively on Latin authors - such as Jerome, Augustine, and Gregory - whose writings contain substantial discussion of hermeneutics and who were known, read, and cited in the Middle Ages and beyond. In this collection of essays, leading international experts in the field identify key passages on patristic hermeneutical theory and demonstrate how the works of these authors have been fundamental for Latin traditions of biblical interpretation. Patristic Theories of Biblical Interpretation offers a selective yet comprehensive guide to a previously understudied area.